Adverse Childhood Experiences and Early Initiation of Marijuana and Alcohol Use: The Potential Moderating Effects of Internal Assets. (24th August 2018) - Chatterjee, Debanjana; McMorris, Barbara; Gower, Amy L.; Forster, Myriam; Borowsky, Iris Wagman; Eisenberg, Marla E.
ABSTRACT: Introduction : Early adolescence is a critical risk period for initiation of substance use. Internal assets (IAs), which are individual qualities guiding positive choices, and adverse childhood experiences (ACEs) are important protective and risk factors, respectively, against substance use. The purpose of this study is to investigate whether IAs modify associations between ACEs and early initiation of alcohol and marijuana use. Method : Data were from 9th and 11th graders who completed the 2013 Minnesota Student Survey ( n = 79, 339). Students reported on experiences of abuse, household dysfunction, and substance use. Multivariable logistic regressions examined associations between different types of ACEs and substance use. Interactions between IAs and ACEs were added to models to test effect modification. For significant interactions, main effects models were re-estimated at different percentiles of IAs. Result : IAs moderated associations of both abuse and household dysfunction with early initiation of marijuana ( p <.003) and alcohol ( p =.007) for females but not for males. For females with low IAs, odds of early initiation of marijuana were approximately twice as high as students without any ACEs. A similar pattern was detected for females' initiation of alcohol use. No effect modification was detected for IAs and experiencing only abuse or household dysfunction on initiation. Conclusion : Special attention should be paid to improving IAs among girls who have already experienced ACEs. Future research should examine protective factors that buffer the effects of ACEs for boys.